2021
DOI: 10.3389/fpsyg.2021.738117
|View full text |Cite
|
Sign up to set email alerts
|

Does Transition to Retirement Promote Grandchild Care? Evidence From Europe

Abstract: Evolutionary theory posits that grandparents can increase their inclusive fitness by investing in their grandchildren. This study explored whether the transition to retirement affected the amount of grandchild care that European grandparents provided to their descendants. Data from five waves of the longitudinal Survey of Health, Aging, and Retirement in Europe collected between 2004 and 2015 from 15 countries were used. We executed within-person (or fixed-effect) regression models, which considered individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Similar results are reported by Backhaus and Barslund (2021) and Zanasi et al (2020) for the European context. Tanskanen et al (2021) , focusing on retirement transition, found a positive effect on grandchild care both for grandfathers and grandmothers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are reported by Backhaus and Barslund (2021) and Zanasi et al (2020) for the European context. Tanskanen et al (2021) , focusing on retirement transition, found a positive effect on grandchild care both for grandfathers and grandmothers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, social family changes occurring in Spanish society and other countries showed a growing number of grandparents are now taking on the parenting role for their grandchildren, thus foregoing the traditional grandparent/grandchild relationship [ 32 , 33 , 34 ]. This often means taking on responsibility for the day-to-day maintenance of a home, schedules, meals, homework, and play dates [ 35 , 36 , 37 ]. This role could influence the time available for doing physical activity or good adherence to MD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, retirement usually increases the amount of spare time one has, and may encourage older individuals to adopt compensatory productive roles in other fields of life. For example, the loss of the role as an employee in the labor market following retirement may lead to increased frequency of volunteering (Tanskanen et al, 2021a) and provision of intergenerational help (Tanskanen et al, 2021b).…”
Section: Who Provides Informal Help?mentioning
confidence: 99%